Outside Front Cover: Volume 3 Issue 3. Issue 3 (24th August 2022) - Luo, Yang; Wu, Donghai; Li, Zehui; Li, Xiao‐Yan; Wu, Yinghong; Feng, Shien‐Ping; Menon, Carlo; Chen, Houyang; Chu, Paul K.
Abstract : Outside front cover image : In the field of catalysis, the intentional introduction of defects is an advanced material design strategy. In this work, plasma functionalized defective MoSe2 is prepared for electrochemical sensing of H2 O2 . The tailored Se vacancies and N dopants generate new active sites, expose more edge active surfaces, narrow the bandgap, and strengthen binding with OH. The sensor delivers competitive sensing performance in an ultra‐wide pH range and a portable SPE sensor is developed to demonstrate the significant commercial potential. This work provides insights into plasma surface modification of 2D catalytic materials. (DOI: 10.1002/smm2.1089 )